See: How Indonesian Student Writers Use Directives in Academic Texts - Ishak, Cita Nuary; Basthomi, Yazid; Widiati, Utami; Hidayati, Maria; Yannuar, Nurenzia (Journal of Education and e-Learning Research, 2021)
This study investigates the roles and functions of directives in academic texts mainly produced by Indonesian college students. Sixty-two (62) imperatives, 11 “it is + Adjective + to”-clauses, and 7 modals of obligation are searched for in academic texts taken from the Corpus of State University of Malang Indonesian Learners English (C-SMILE) and the Corpus of Indonesian Texts in Academia (CINTA). As a point of comparison, we use the Corpus of Contemporary American English (COCA). We found that the corpora are similar regarding the high frequency of occurrences of the imperative see, among other directives. However, the corpora differ with regards to the functions of the imperative see. Whilst see in COCA plays an important role in directing readers to both internal and external sources, see in C-SMILE and CINTA is used exclusively to refer to internal resources. This suggests a lack of access on the part of Indonesian undergraduates’ to necessary reading materials. In addition, other directives, such as cognitive imperatives, are rarely used in the Indonesian corpora. The low frequency of cognitive imperatives indicates that the practice of inviting readers to develop their mental process of understanding has not been well established in Indonesian academic culture. These findings suggest the need to introduce to Indonesian student writers, various ways of engaging readers into texts.